The Map of Padua by Giovanni Valle: Hypertext/Hyper-Representation Ante Litteram (diségno, 2019)
The city of Padua is surveyed by technicians coordinated by Giovanni Valle, who elaborates, draws and ‘amends’, under the direction of Simone Stratico –whose role has not yet been clarified [1]– a map that was engraved in Rome, within 1784, by Giovanni Volpato. For technical reasons the huge surface of the drawing is transfered on 20 copper plates of various sizes [Ghironi, Mazzi 1985] becoming, in its original edition, one of the most important and famous maps of the city. Realized according to precise criteria of geometric measurement, it can be considered, therefore, a punctual record of the urbancondition of Padua in the 18th century [Zaggia 2009]. (read more)